Influence of step aerobics training programme on chosen dimensions of morphological status in males - Sekulić, Damir (Kinesiologia Slovenica, 2001)
The aim of the research was to establish the transformation effects of step aerobics programme on selected morphological parameters among 26 male subjects, participants of the programme. The programme consisted of 25 step aerobics traing sessions and lasted for nine weeks. The subject of analysis was changes in four variables concerning the thickness of skin fold and four circumferences of corresponding parts of the body. Multivariate analysis of variance revealed a satisfying level of significance of differences in morphological dimensions, which can be represented by noteworthy changes in two selected variables (abdominal skin fold and thigh skin fold). We assume that changes in circumferences of selected body parts did not reach the satisfying level of significance because of minor muscle hypertrophy, which compensated the decrease caused by reduction of the subcutaneous fatty tissue.
Keywords: morfologija; morfološke lastnosti; moški; raziskave; step aerobika